Reproduction and morphology of Central American and Tres Marias spinner dolphins in the eastern tropical Pacific. Issue 1 (27th October 2018) - Chivers, Susan J.; Perryman, Wayne L.; Lynn, Morgan S.
Abstract: Four geographic forms of spinner dolphin ( Stenella longirostris ) occur in the eastern tropical Pacific. Two of the forms are pelagic: the eastern and whitebelly, and two are coastal: the Central American and Tres Marias spinner dolphins. Of these, only the Tres Marias form lacks recognition appropriate for developing management and conservation plans. Vertical aerial photographs of 57 spinner dolphin schools taken between 1988 and 2006 were used to examine the range of coastal forms and to characterize their calving seasons. On the basis of adult body length, spinner dolphins photographed off Guerrero, Mexico, were identified as those of the Central American form, which is north of their known range, and those photographed farther north, approximately 112 km off Nayarit, Mexico, were identified as the Tres Marias form. Calving peaked from October through March, and there was evidence that calving seasons differed among geographic forms with coastal forms calving later than pelagic forms. We present the first life history parameter estimates for the coastal forms of spinner dolphins, provide additional support for recognition of the Tres Marias form, and the first evidence of the Central American form occurring north of the Gulf of Tehuantepec, Mexico.